Influência da temperatura na resistividade elétrica e na cinética de corrosão da armadura de concretos contaminados com cloretos - Lucas Chaves Chiaradia (2023)
The corrosion of reinforcement in concrete structures is a serious and costly problem for the construction sector. Several factors influence the evolution of the corrosive process, as well as the interpretation of the results obtained by techniques for evaluation and monitoring of reinforcement corrosion. These factors can be intrinsic, such as the composition of the cement and the porosity of the concrete, or extrinsic, such as environmental conditions and the level of environmental aggressiveness to the concrete structure. In the case of temperature, its variation alters the ionic mobility in the microstructure of the cementitious matrix, favoring or hindering the electrochemical process. This research evaluated the influence of temperature on the electrical resistivity of concrete and on the corrosion kinetics of the reinforcement, both subject to chloride action. Specimens of reinforced and non- reinforced concrete produced with a water/cement ratio of 0.60 and 0.45, with and without NaCl contamination, were evaluated, at a content of 1.00% of chlorides in relation to the cement mass. The concretes were physically and mechanically characterized at 28 and 90 days of age. After 204 days, the reinforced specimens contaminated with chlorides presented active corrosion states, verified by triplicate tests of corrosion potential and linear polarization. Then, the samples were submitted to temperature cycles, ranging between 55°C and -5°C, in a round trip cycle, to determine electrical resistivity, corrosion potential and corrosion speed. By the tests of linear polarization and corrosion potential, at higher temperatures, with a consequent decrease in electrical resistivity, it was observed significant variability of the results and difference between the results of the concretes contaminated with chlorides in relation to the non-contaminated ones. Differently, at lower temperatures, the results between the uncontaminated and contaminated specimens approached, remaining in the region of low probability of corrosion, regardless of whether or not the reinforcement was depassivated. This was more evident in the measurements carried out at a temperature of -5°C, when a low probability of corrosion was recorded, through the corrosion potential test, and a negligible level of corrosion, through linear polarization test, both for the chloride and non-chloride specimens. As for electrical resistivity, the opposite was observed, since the largest variations were recorded at low temperatures and at higher temperatures the electrical resistivity values of the all mix proportions studied were closer, indicating a risk of moderate to high corrosion. Correlating the results of corrosion potential and corrosion rate, varying the temperature, a similar trend was noticed in relation to the interpretation of corrosion kinetics, that is, when the potential decreases, the corrosion rate increases. The linear and exponential correlations obtained between electrical resistivity and temperature and between corrosion rate and temperature, respectively, showed that there is a very strong correlation between the confronted variables, since the correlation coefficients were between 0,95 and 0,99. The research showed that temperature variation influences the electrical resistivity of the concrete, modifying the kinetics of reinforcement corrosion in concretes contaminated with chlorides.